Efficacy of physical and chemical disinfection against clinically relevant free-living amoebae isolated from drinking water and plumbing biofilms - Nisar, Muhammad Atif; Hayward, Claire; Ross, Kirstin E.; Brown, Melissa H.; Bentham, Richard; Whiley, Harriet (Frontiers in Microbiology, 2025)
IntroductionFree-living amoebae (FLA) are commonly found in drinking water systems and biofilms, posing public health risks both as pathogens and as hosts for opportunistic bacteria such as Legionella spp. and Mycobacterium spp. Current water management practices are often insufficient to control biofilm-associated FLA and their intracellular pathogens.MethodsThis study evaluated the efficacy of multiple disinfectants—thermal disinfection (70 °C), hydrogen peroxide, 2-methyl-4-isothiazolin-3-one, benzalkonium chloride (BAC), sodium hypochlorite, and chlorine dioxide—against planktonic trophozoites and cysts of five FLA strains: Acanthamoeba DB1, Allovahlkampfia DS1, Stenamoeba DS1, Vermamoeba vermiformis HB7, and Acanthamoeba polyphaga ATCC® 30461™. Disinfectants were tested at varying concentrations and exposure times.ResultsThermal disinfection was the most effective treatment, followed by hydrogen peroxide. Exposure to 70 °C for 45 min achieved >4 log10 reduction of all FLA trophozoites. Thermal treatment at 70 °C for 60 min produced >4 log10 reduction for all cysts except V. vermiformis HB7, which showed greater thermal tolerance.DiscussionThe findings demonstrate that thermal disinfection is a highly effective strategy for inactivating multiple FLA species in their trophozoite and cyst forms. Further research is needed to evaluate the feasibility and effectiveness of applying these strategies to control biofilm-associated FLA within plumbing fixtures and drinking water distribution systems.